Ultrasound-Attenuated Microorganisms Inoculated in Vegetable Beverages: Effect of Strains, Temperature, Ultrasound and Storage Conditions on the Performances of the Treatment - Campaniello, Daniela (Microorganisms, 2020)
Four microorganisms (Lactobacillus acidophilus LA5, Bifidobacterium animalis subsp. lactis DSM 10140 and Lactiplantibacillus plantarum c16 and c19) were attenuated through ultrasound (US) treatments (40% of power for 2, 4 and 6 min; and 60% for 2 min; pulses were set at 2 s) inoculated in rice–oats–almond–soy-based beverages and stored at 4 °C for eight days. All strains were able to survive throughout the storage independently by the food matrix. Concerning the effect on acidification, the results were analyzed through multifactorial analysis of variance (MANOVA) and the key-findings of this were: (i) The treatment with 40% of power for 6 min was the most efficient at delaying acidification; (ii) Lb. acidophilus LA5 showed the best capacity to delay acidification; (iii) in the soy-based beverage a lower acidification was found. In a second step, L. plantarum c16 and c19 were attenuated, inoculated in rice beverage, stored under a thermal abuse (for 4 and 24 h) and then at 4, 15 and 20 °C. The results showed that only when US were combined with refrigeration temperatures were they efficient at delaying acidification. Thus, a perspective for attenuation could be the optimization of the treatment to design an effective way to counteract acidification also under a thermal abuse.